2018
DOI: 10.1186/s13018-018-0967-y
|View full text |Cite
|
Sign up to set email alerts
|

The potent anti-inflammatory effect of Guilu Erxian Glue extracts remedy joint pain and ameliorate the progression of osteoarthritis in mice

Abstract: BackgroundOsteoarthritis (OA) is a slow progressing, degenerative disorder of the synovial joints. Guilu Erxian Glue (GEG) is a multi-component Chinese herbal remedy with long-lasting favorable effects on several conditions, including articular pain and muscle strength in elderly men with knee osteoarthritis. The present study aimed to identify the effects of Guilu Erxian Paste (GE-P) and Liquid (GE-L) extracted from Guilu Erxian Glue in anterior cruciate ligament transection (ACLT)-induced osteoarthritis mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
(58 reference statements)
3
13
0
Order By: Relevance
“…Because type 2 diabetes mellitus frequently co-exists with osteoarthritis ( Veronese et al, 2019 ), Gui-Lu-Er-Xian-Jiao is often given to support the kidney yin and yang for patients with diabetes. This herbal formula can mitigate chondrocyte degeneration, cartilage destruction, and articular pain ( Tsai et al, 2014 ; Chou et al, 2018 ). The current study identified high-dose RCEG and other drugs that are often co-prescribed with it for type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Because type 2 diabetes mellitus frequently co-exists with osteoarthritis ( Veronese et al, 2019 ), Gui-Lu-Er-Xian-Jiao is often given to support the kidney yin and yang for patients with diabetes. This herbal formula can mitigate chondrocyte degeneration, cartilage destruction, and articular pain ( Tsai et al, 2014 ; Chou et al, 2018 ). The current study identified high-dose RCEG and other drugs that are often co-prescribed with it for type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo setting of anterior cruciate ligament transection (ACLT)-induced OA, the effects of a 28-days intervention with GE in the form of either paste or liquid were evaluated in two treatment doses (100 mg/kg/day or 300 mg/kg/day) [42] against phosphate-buffered saline and celecoxib (10 mg/kg/day). Notably, the intervention with the liquid mixture formulation in the minimum dose was able to considerably lessen the mRNA levels of IL-1β, IL-6, and TNF-α, as well as the protein expression of IL-1β and TNF-α, compared to either formulation at high dose and celecoxib [44]. Both formulations presented a notable and dose-dependent reduction of osteolytic lesions, cartilage erosion, and bone spur formation in addition to reductions observed in proteoglycan, chondrocyte, and cartilage damage [44].…”
Section: Guilu Erxian Gluementioning
confidence: 95%
“…Notably, the intervention with the liquid mixture formulation in the minimum dose was able to considerably lessen the mRNA levels of IL-1β, IL-6, and TNF-α, as well as the protein expression of IL-1β and TNF-α, compared to either formulation at high dose and celecoxib [44]. Both formulations presented a notable and dose-dependent reduction of osteolytic lesions, cartilage erosion, and bone spur formation in addition to reductions observed in proteoglycan, chondrocyte, and cartilage damage [44]. Although the formulations of this mixture presented chondroprotective properties with anti-inflammatory characteristics, the evidence supporting those allocations remain inconclusive.…”
Section: Guilu Erxian Gluementioning
confidence: 95%
See 2 more Smart Citations